1 - Participatory Action Research as a Platform for Community Engagement in Higher Education - Godwell Nhamo (Journal of Higher Education in Africa, 2012)
Institutions of higher education throughout the world have reached con- sensus in terms of their core business, defined through: (1) teaching and learning, (2) research and (3) community engagement. Of these three areas of focus, community engagement has posed serious challenges in terms of clear cut methodologies and measurability. While the ‘why’ question of com- munity engagement may be understood, the ‘how to do it’ questions need attention. This has also raised anxiety amongst staff, who are expected to perform and get rewards for community engagement. It is against this back- ground that this article argues for Participatory Action Research (PAR) as an enabling platform for community engagement in higher education. The argument and assumption is that PAR provides a two-way engagement process that locks in both the researchers and communities they will be reaching, in seeking to solve community problems. PAR moves higher edu- cation from linear-oriented research to web-oriented systematic cycles of inquiry that involve planning, asking questions, taking action, observing, evaluating and critically reflecting, prior to planning the next cycles. Com- munity problems that could be addressed through PAR include those aris- ing from environmental damage (including climate change), HIV and AIDS, lack of service delivery, politics and many more.